MASALAH PENGADAAN TANAH UNTUK PEMBANGUNAN PLTU DI BATANG - Aziz, Achmad Taqwa (BHUMI: Jurnal Agraria dan Pertanahan, 2018)
The availability of land is important element in development activitiesespecially for public interest. This study aims to determine the mechanisms applied in land acquisition for Batang Power Plant, in Batang, Central Java; and to explore the supporting and inhibiting supports in the implementation of the land acquisition and settlement efforts. This study explains development of Batang Power Plant as infrastructure projects use the mechanism of Public Private Partnerships (PPP), according to The Law No. 30 of 2009 on Electricity and Presidential Decree No. 13 of 2010. The supporting factors of the implementation of land acquisition are existence of a positive perspective of residents, the price of the deal, the full support of government and large investment funds. The inhibiting factors of the implementation of the land acquisition are the attitude of the citizens of rejection, the price disagreement, the issue of environmental pollution and the emergence of land speculators. For resolving obstacles and constraints in land acquisition created the establishment of a forum of communication together, increasing participation of citizens, transparency and accountability, creating guarantees the survival of the farm laborers and tenants, and enhancing community empowerment through CSR programs. Keywords: Acquisition of land, the power plant.